Programming on audio signal processing - Ong, Kevin Zhen Wei (2017)
MP3 is one of the most commonly used form of Audio Signal Processing today. It is important as a student in audio signal processing to understand the theories and concepts behind this technology. In this report, the basic theories behind the MP3 technology are explained and some of the codes are implemented and presented in a visual format to allow the student to be able to visualize how the MP3 algorithm affects the audio signal. The final output of this project is the creation of a simple Graphical User Interface to help students to improve their understanding of the various steps used in the MP3 Algorithm.